Late Quaternary climatic variability in the Central Ganga Plain: A multi-proxy record from Karela Jheel (Lake). (10th July 2017) - Tripathi, Deepika; Chauhan, Devendra Kumar; Farooqui, Anjum; Kotlia, Bahadur Singh; Thakur, Biswajeet; Morthekai, P.; Long, Tengwen; Chauhan, Mohan Singh; Pokharia, Anil Kumar
Abstract: A multi-proxy study involving phytoliths, diatoms, thecamoebians and sponge spicules was carried out on a trench profile (260 cm deep) from Karela Lake in the Central Ganga Plain to reconstruct climatic variations since ca. 17, 000 cal BP. The testate amoebae record indicate spells of winter monsoon between ca. 17, 000 cal BP and 13, 700 cal BP. Increased diversity of diatoms, testate amoebae and sponge spicules, in addition to low Humidity/Aridity Index (Iph) values suggest strengthened monsoon inducing the expansion of lake margin and high primary productivity during ca. 13, 700 to 4300 cal BP. Further between ca. 4300 and 2900 cal BP, higher Iph values and related responses of other studied proxies show a stressed lake ecosystem. Since ca. 2900 cal BP, area of the lake was reduced responding to low intensity of the Indian Summer Monsoon. Anthropogenic activities may also have played a role in the lake shrinking at least during some parts of this duration.